Políticas de livros didáticos: empresariamento e instrumentalização da educação escolar - Seemann, Vanessa Eliza (2023)
This research, linked to the Educational Policies line, focused on textbook policies in elementary education. Its objectives were to analyze the role of the State in the construction of national textbook policy; historicize the national textbook policy until the formulation of the National Textbook Plan (PNLD); analyze the expansion of the business sector in the field of production and sale of teaching materials, as well as analyze the instrumentalization of teaching materials in educational processes. To achieve these objectives, the research was guided by the following questions: What policies guided the choice of textbooks in Brazil? How are they selected to receive government support? How many resources are invested in these materials? How do textbooks contribute to or create pedagogical problems in teaching work at school? What do the data show about the expansion of companies that produce textbooks? To address these issues, a methodological approach was used based on three dimensions: (a) in the bibliographic production of researchers who problematize the topic of books and teaching materials; (b) in the regulations that deal with textbook policies and, (c), in statistical data relating to the quantity of textbooks produced for different levels of basic education and the amounts invested by governments. The dissertation is organized into three chapters, in addition to initial and final considerations. The first chapter, called: Educational policies and textbooks, addresses educational policy issues relating to textbooks in Brazil and public investment in the purchase and distribution of these materials to public schools. It also addresses the history of the National Textbook Program in Brazil and the paths taken by this policy from the 19th century to the present day. It also presents the course of textbooks from their production to their arrival at school, indicating the long journey from evaluation to printing and distribution of books in public basic education networks. In this sense, there is significant growth in publishing companies and imposing public investments in this program. In the second chapter, called: The standardization of textbooks, a reflection is developed around the textbook and how this resource gained centrality in educational practice. It was observed that there are risks of teachers being mere executors of teaching texts produced by companies that universalize the content throughout the country. Furthermore, in this chapter, the practice of publishers in public schools and the business of textbooks in Brazil is discussed. In the third chapter, called Possibilities and limits of textbooks in teaching practice, issues relating to the use of textbooks are addressed, highlighting how this material has gained centrality in many schools and education networks. It is also elucidated how many teachers stopped being teachers to be mere executors of didactic texts. Finally, we highlight some challenges for a new positioning of textbooks and the challenges that these materials have faced in relation to the diversity of schools and students, as well as the expansion of technological resources. The research reached the following conclusions: (a) the textbook needs to keep up with current demands, incorporating new methodologies and technologies; (b) it is necessary to consider important aspects for the quality of teaching, such as continued training and the appreciation of education professionals; the relevance of elements such as teacher training, school infrastructure, access to technological resources and innovative pedagogical practices in promoting educational quality must be taken into account. In short, textbooks, although important, should not be seen as the only tool in the educational process.